Seasoned equity offerings (SEO) on stock returns: An event study on the Philippine context - Romero, Frederick P. (Animo Repository, 2017)
Companies issuing a secondary equity shares obtain additional funds from the public and simultaneously change their capital structure. The funds that can be obtained from this capital raising can be used by the company on its growth plans and expansion goals which can eventually add value to the company. This paper examines the short-term effect of the announcement of SEOs to the market valuation of the issuing firms. Using the Event Study methodology, this paper calculates the Cumulative Average Abnormal Returns of the companies across the 3-day, 7-day, 11-day, 21-day and 31-day event windows surrounding the event date using the Generalized Rank Test at the 0.01, 0.05 and 0.10 significance level. The study focuses on five (5) major industries namely Energy, Materials, Property, Financials and Consumer Staples. The paper found negative significant impact of the SEO announcement on the Energy and Property industries signaling the negative news brought about by the corporate event. However, the Materials sector experienced significant positive abnormal returns indicating that investors view the news as something that will be beneficial to the overall value of the company. Lastly, the paper found insignificant effect of SEO announcements on the companies under the Consumer Staples and Financials industries. The study suggests that corporate actions such as SEO can be important information on certain industries/sectors that investors can use in order for them to better manage their portfolio investments and overall return. © 2017 American Scientific Publishers. All rights reserved.